Metameric variation of upper molars in hominoids and its implications for the diversification of molar morphogenesis. Issue 138 (January 2020) - Morita, Wataru; Morimoto, Naoki; Kono, Reiko T.; Suwa, Gen
Abstract: Metameric variation of molar size is in part associated with the dietary adaptations of mammals and results from slight alterations of developmental processes. Humans and great apes exhibit conspicuous variation in tooth morphology both between taxa and across tooth types. However, the manner in which metameric variation in molars emerged among apes and humans via evolutionary alterations in developmental processes remains largely unknown. In this study, we compare the enamel-dentine junction of the upper molars of humans—which closely correlates with morphology of the outer enamel surface and is less affected by wear—with that of the other extant hominoids: chimpanzees, bonobos, gorillas, orangutans, and gibbons. We used the morphometric mapping method to quantify and visualize three-dimensional morphological variation, and applied multivariate statistical analyses. Results revealed the following: 1) extant hominoids other than humans share a common pattern of metameric variation characterized by a largely linear change in morphospace; this indicates a relatively simple graded change in metameric molar shape; 2) intertaxon morphological differences become less distinct from the mesial to distal molars; and 3) humans diverge from the extant ape pattern in exhibiting a distinct metameric shape change trajectory in the morphospace. The graded shape change and lower intertaxon resolution from the mesial to distal molars are consistent with the concept of a 'key' tooth. The common metameric pattern observed among the extant nonhuman hominoids indicates that developmental patterns underlying metameric variation were largely conserved during ape evolution. Furthermore, the human-specific metameric pattern suggests considerable developmental modifications in the human lineage.